The Influence of Managerial Cognitive Capabilities and Absorptive Capacity on Entrepreneurial Intention through Strategic Intention Capability among the Alumni of Cak and Ning Surabaya - Suprapto, Widjojo; Endrata, Michael Audrey; Johannes, Joy (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2025)
This study explores the entrepreneurial potential of Cak dan Ning Surabaya alumni by analyzing the influence of Managerial Cognitive Capabilities and Absorptive Capacity on Entrepreneurial Intention, mediated by Strategic Intuition Capability. Cak dan Ning is a cultural ambassador program in Surabaya that grooms local youth to represent the city’s identity, tourism, and values. Although no longer actively involved in public engagements after their tenure ends, many alumni face the challenge of remaining professionally relevant. Therefore, this study investigates how their managerial and absorptive competencies contribute to fostering entrepreneurial mindsets. Using a quantitative explanatory approach, data were collected from 132 alumni respondents via an online questionnaire and processed using SmartPLS 4.0. The findings reveal that Managerial Cognitive Capabilities significantly influence both Strategic Intuition Capability and Entrepreneurial Intention. Additionally, Absorptive Capacity has a significant effect on Strategic Intuition Capability, but not on Entrepreneurial Intention. Strategic Intuition Capability also does not significantly mediate the relationship between both Managerial Cognitive Capabilities and Absorptive Capacity with Entrepreneurial Intention. These results highlight the need for targeted empowerment strategies to help Cak dan Ning alumni channel their acquired skills and cultural insights into sustainable entrepreneurial ventures, ensuring their continued contribution to society beyond their ambassadorial roles.